2023
DOI: 10.3389/fnsys.2023.1160083
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar contribution to the regulation of defensive states

Abstract: Despite fine tuning voluntary movement as the most prominently studied function of the cerebellum, early human studies suggested cerebellar involvement emotion regulation. Since, the cerebellum has been associated with various mood and anxiety-related conditions. Research in animals provided evidence for cerebellar contributions to fear memory formation and extinction. Fear and anxiety can broadly be referred to as defensive states triggered by threat and characterized by multimodal adaptations such as behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 131 publications
(174 reference statements)
0
1
0
Order By: Relevance
“…Recent studies have revealed that the cholecystokinin-expressing hypothalamic PMD cells projecting to the DLPAG control escape behavior induced by a range of innate threats ( Wang et al, 2021a ). Additionally, the fastigial nucleus-VLPAG pathway has been found to regulate learned defensive responses by modulating the association between conditioned and unconditioned stimuli, thus influencing memory formation ( da Silva et al, 2023 ).…”
Section: Main Functional Characteristics and Mechanisms Of Pagmentioning
confidence: 99%
“…Recent studies have revealed that the cholecystokinin-expressing hypothalamic PMD cells projecting to the DLPAG control escape behavior induced by a range of innate threats ( Wang et al, 2021a ). Additionally, the fastigial nucleus-VLPAG pathway has been found to regulate learned defensive responses by modulating the association between conditioned and unconditioned stimuli, thus influencing memory formation ( da Silva et al, 2023 ).…”
Section: Main Functional Characteristics and Mechanisms Of Pagmentioning
confidence: 99%